Problem Based Learning Models in Senior High Schools: A Literature Review on Learning Physics - Rachmadaniz Audrey Kinasih; Rosikhotul Ilmi; Nindy Carmelia; Anisa Rizky; Binar Kurnia Prahani; Rizki Fitri Rahima Uulaa (IKIP Widya Darma Surabaya, 2023)
Objective: One of the facilities and infrastructure to improve the quality of human resources in education. The challenge must be to create the nation's next generation who can solve a problem, can think creatively, can think critically and make decisions. The way to improve student’s abilities is to use an interactive and not monotonous learning model to make physics learning more effective. The purpose of the research is to investigate the benefits of the PBL learning model in senior high school physics instruction and the influence it has on those subjects. Method: In addition, the research method used examines the literature and collects data from 15 articles from various journals. These both national and international scientific journals that are aligned with the problem-based learning model, which is then analyzed descriptively and qualitatively. Results: The conclusions that can be drawn through this research is that a problem-based learning model is very effective for applying to physics subjects in high school. Novelty: Increased student learning outcomes critical thinking, problem-solving skills and understanding of physics concepts evidence this.